IRI 2001/90 TEC predictions over a low latitude station - Scida, Luis Alberto (2009)
Total electron content (TEC) over Tucumán (26.9°S, 294.6°W) measured with Faraday technique during the high solar activity year 1982, is used to check IRI 2001 TEC predictions at the southern crest of the equatorial anomaly region. Comparisons with IRI 90 are also made. The results show that in general IRI overestimates TEC values around the daily minimum and underestimates it the remaining hours. Better predictions are obtained using ground ionosonde measurements as input coefficients in the IRI model. The results suggest that for hours of maximum TEC values the electron density profile is broader than that assumed by the model. The main reason for the disagreement would be the IRI shape of the electron density profile. In a previous work using TEC measurements over Tucumán, obtained from GPS satellite signals during the high solar activity year 1999, a better agreement between IRI predictions and measurements has been observed. That better agreement was produced by the fact that 1999 GPS TEC measurements are 50% lower than those obtained by Faraday rotation technique during 1982. An equator ward movement of the southern peak of the EA plus the minor ionization level in 1999 could produce this reduction in TEC values. Moreover, it can be seen that in most of cases IRI TEC values around daily minimum show an hour displacement with respect to the experimental data.